1999
DOI: 10.1002/(sici)1098-2744(199905)25:1<42::aid-mc5>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Rare mutations ofp53, Ki-ras, and ?-catenin genes and absence of K-sam and c-erbB-2 amplification inN-methyl-N?-N-nitrosoguanidine-induced rat stomach cancers

Abstract: Rat stomach cancers induced by N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) have been widely used as a model for human stomach cancers of the differentiated type. However, there has been little information regarding their molecular basis. In this study, we examined the genetic alterations reported in human stomach cancers in 10 rat stomach cancers that had been induced in male ACI/N rats by administering MNNG in the drinking water. One of the 10 cancers had a mutation of the p53 gene at the second position of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
3
10
1
Order By: Relevance
“…Regarding the mutational activation of oncogenes, in our previous study, Kras2 point mutations were absent, and Catnb mutations were present only in high‐grade lesions. ( 6,7 ) The absence of Kras2 mutations was also confirmed in the 21 tumor samples here by sequencing Kras2 codons 12, 13 and 61 (data not shown). ( 7 )…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Regarding the mutational activation of oncogenes, in our previous study, Kras2 point mutations were absent, and Catnb mutations were present only in high‐grade lesions. ( 6,7 ) The absence of Kras2 mutations was also confirmed in the 21 tumor samples here by sequencing Kras2 codons 12, 13 and 61 (data not shown). ( 7 )…”
Section: Discussionsupporting
confidence: 58%
“…( 7 ) With regard to the inactivation of tumor‐suppressor genes, Trp53 ( p53 ) mutations were infrequent (1/10), and microsatellite instability was absent. ( 7 )…”
mentioning
confidence: 99%
“…Hirayama et al reported no amplification of K-sam or cerbB-2 in 7 rat adenocarcinomas (Hirayama et al, 1999b) and no microsatellite alterations in 12 loci in nine cases (Hirayama et al, 1999b). CONCLUSIONS Many animal models for stomach cancers have been established using rats, dogs, and mice.…”
Section: Other Gene Alterationsmentioning
confidence: 99%
“…[16][17][18][19][20] However, there has been little information generated regarding the molecular basis of the process. We previously examined genetic alterations that have been reported in human stomach cancers, using DNA samples extracted from cancers 21) and observed only a few (one in 10 cancers) mutations of the p53 gene at the second position of codon 171 (Val→Glu) and no mutations in codons 12, 13, or 61 of Ki-ras or in the N-terminal phosphorylation sites of the β-catenin gene. Furthermore, there was no apparent amplification of the K-sam or c-erbB-2 genes and no microsatellite alterations.…”
mentioning
confidence: 99%